Pengaruh Media Sosial Marketing dan Inovasi Produk terhadap Ewom Serta Keputusan Pembelian: Studi Coffee Baracks Kabupaten Bogor - Syafrudin wibowo, Teguh; Sumarwan, Ujang; Aminah, Mimin (IPB University, 2025)
The Indonesian coffee industry has experienced dynamic growth, driven by rising coffee consumption and increasing internet penetration. Coffee Baracks in Bogor Regency aims to utilize social media marketing and product innovation to influence consumer purchase decisions, with electronic word-of-mouth (eWOM) serving as a mediator. This study analyzes the impact of these factors on digital-era purchasing decisions, specifically examining how social media marketing (Instagram) and product innovation affect eWOM and purchase decisions, while also investigating eWOM's mediating role in strengthening these relationships. Using a quantitative approach, data was collected through questionnaires distributed to 200 respondents, consisting of Coffee Baracks' Instagram followers and direct visitors. The data was analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) via SmartPLS 3.3.3. The results indicate that social media marketing has a significant positive effect on purchase decisions (path coefficient: 0.192; p < 0.05). Conversely, product innovation shows a negative impact (-1.021; p < 0.05), suggesting misalignment with market preferences. However, when mediated by eWOM, product innovation demonstrates a strong positive influence (1.493; p < 0.05). Additionally, eWOM strengthens the relationship between social media marketing and purchase decisions (0.196; p < 0.05) and has a direct positive effect (1.700; p < 0.05). The findings suggest that effective social media marketing strategies and eWOM management significantly enhance purchase decisions, while product innovation must align with market expectations. Practical implications recommend that Coffee Baracks focus on creative social media content, market research for product innovation, and maximizing positive reviews through eWOM.